Comportamiento agronómico de tres leguminosas en el centro experimental la playita - Moreira Quiñonez, John Alejandro (2015)
This research was conducted at the Experimental Farm "La Playita", Technical University of Cotopaxi, The cantonal head is based on an ancient alluvial river terrace San Pablo (WGS 84 Location: Latitude S0 ° 56 '27 " W Longitude 79 ° 13 '25 ", height 220 m). With a duration of 60 days. As a general objective we determine the agronomic performance of three legumes in the Experimental Center La Playita. Design of randomized complete block (RCBD) with four treatments and five replicates for a total of 20 experimental plots of 2 x 1.5m was used. The separation between treatment means was performed by multiple range test of Tukey at 5% probability. As a result we have Analyzing the root weight (g) it can be seen that the highest root weight (g) reflected in the Kudzu legume 21.50 (g). The major findings in relation to the weight of the obtained g forage legume Kudzu 50.83 g; also be noted that most coverage at 60 days with Kudzu legume is reflected with 41.67%; followed by coverage at 120 days with 60.00% in the Kudzu legume. The analysis for the total aerobic colony forming units obtained the highest content the Kudzu legume with 6.31 (UFC); while for the analysis used to fungi and yeasts Kudzu legume obtained the highest value 5.78 (UFC). The higher soil nutrient obtained in the agronomic performance obtained with the parameter P 174.00 ppm specifying it as high in black legume Mucuna; regarding Mucuna mostly white reflection in the nutrient parameter interpreting as high with 126.00 ppm Fe; Kudzu legume with the parameter used to 86.00 ppm Fe indicating it as high and the Fallow most results fell to 48.00 ppm Fe parameter determining it as high.